Dilemmas, pained frustration, and new possibilities: masculinities, violences, and disabilities - Myrttinen, Henri (Interconnecting the violences of men, 2025)
Disabled masculinities pose a theoretical and, more importantly, a very visceral, real-life dilemma for many men. This dilemma arises from disability being linked with being reliant on others, feeble and defenceless, yet masculinity is primarily associated with being physically strong, healthy, dominant, and independent. Violence can play an ambiguous role in disabled men’s lives. Some men may have become disabled through their participation and/or exposure to violence, such as in war; men with disabilities may be more exposed to various forms of violence; living with disabilities may lead to violent, negative, ‘coping’ strategies against others and oneself; but disabilities can also lead some men re-assessing their masculinities and adopting more caring ways of being a man. This chapter seeks to explore these dilemmas, vulnerabilities, as well as shifts in masculinities and their links to violence, both amongst men born with disabilities and those who acquired disabilities later in life. It draws mainly on previous work by the authors in four different contexts: Turkey, Kachin State in Myanmar, South African township, and rural areas of Ghana. We thereby cover areas affected by armed conflict and high levels of criminal violence, as well as areas where these are largely absent.